Development of MESI GUNDA (Plane Shape Educational Game) Based on Android to Support Mathematical Problem-Solving Skills - Arifatun, Vita; Agustyaningrum, Nina; Pradanti, Paskalia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
One of the skills that need to be given to students in learning mathematics is problem solving ability. However, at MTs N 5 Magelang, students' mathematical problem-solving ability is still low. In addition, the problem experienced is the lack of use of interactive learning media and using technology. The purpose of this research is to develop and analyze the validity, practicality, and effectiveness of Android-based MESI GUNDA (gaMe edukaSi banGun Datar or in English Plane Shape Educational Game) learning media to support mathematical problem-solving skills in flat building materials. This research is a type of Research and Development (RnD) with ADDIE model that utilizes Articulate Storyline, Canva, and WEB2APK Builder applications. The validity analysis used an assessment questionnaire from media and material experts consisting of two lecturers and one teacher for media experts, while material experts were carried out by one lecturer and two teachers. The practicality of the product was measured by a practicality questionnaire filled out by students and teachers totaling 27 students and one teacher, while the effectiveness by looking at the increase in pre-test and post-test scores of 23 students who were analyzed using N-gain. The results showed that Android-based MESI GUNDA media is valid, practical, and effective to support mathematical problem-solving skills. MESI GUNDA fulfills the valid aspect with a score of 90 out of 100 with a very valid category by media experts and from material experts obtained a score of 56 out of 65 with a very valid category. The media also meets the practical and effective aspects with a score of 80.59 out of 100 categorized as very practical and an N-gain value of 0.32 categorized as moderate. Therefore, the MESI GUNDA media is recommended for use by teachers to enhance the mathematical problem-solving abilities of junior high school students or their equivalents.